Healthy Eating and Active Living for Diabetes-Glycemic Index (HEALD-GI): A Pragmatic Randomized Controlled Trial. (29th May 2020) - Avedzi, Hayford; Soprovich, Allison; Ramage, Stephanie; Alghamdi, Abdulrhman; Storey, Kate; Johnson, Jeffrey; Johnson, Steven
Abstract: Objectives: Rigorous evidence is needed to support uptake of recommendations to include low glycemic index (GI) foods in daily meal planning as an effective dietary self-care strategy for people with type 2 diabetes (T2D). We evaluated the effectiveness of a 12-week web-based GI-targeted nutrition education intervention on dietary intakes and GI-related knowledge among adults with T2D. Methods: Participants were randomized to a control group ( n  = 34) that received standard printed copies of Canada's Food Guide and Diabetes Canada's GI resources or an intervention group ( n  = 33) that received those same materials, plus an online platform with six self-directed learning modules and supplementary print material. Each module consisted of a customized video, links to reliable websites, chat rooms, and quizzes. Evidence-based GI concept information included GI values of foods and advice for low-GI shopping, recipes, and cooking tips by a Registered Dietitian. Preferred supports through email, text messaging, phone calls, or postal mail to reinforce participants' learning were also provided. The primary outcome, average daily dietary GI intake, was assessed using 3-day food records. Additional measures including GI knowledge and self-efficacy, glycated hemoglobin A1c, lipids, systolic blood pressure, body mass index, waist circumference, and computer proficiency, were assessed at baseline and at three months post-intervention. Results: Participants ( N  = 67) were 64% men; mean (standard deviation [SD]) age 69.5 (9.3) years, with mean diabetes duration of 19.0 (13.7) years, BMI 30.1 (5.7) kg/m 2 and A1c 7.1 (1.2)% at baseline. Mean daily GI intake decreased in the intervention group by 2.79 (7.77) compared to a 0.76 (6.48) increase in the control group (adjusted mean difference [95% CI]; −3.77 [−6.95, −0.58]). Mean GI knowledge 2.14 [0.59, 3.69], understanding of GI concept 1.65 [0.85, 2.44] and self-efficacy for consuming low-GI foods 1.29 [0.51, 2.07] increased among the intervention group ( P  < 0.01) compared with the control group. Conclusions: Web-based GI-targeted education program improved the quality of carbohydrate consumption among adults with T2D and may have been mediated through increases in knowledge and self-efficacy. Web-based nutrition education may be an effective alternative in this population. Funding Sources: Canadian Foundation for Dietetic Research.